2020
DOI: 10.17138/tgft(8)125-132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed storage on seed germination and seedling quality of <i>Festulolium</i> in comparison with related forage grasses

Abstract: Tests of seed germination, seed dormancy and seedling growth were performed on 0-, 6-, 20- and 30-months-old seed lots of Festulolium in comparison with Italian ryegrass (Lolium multiflorum) and meadow fescue (Festuca pratensis). Tests were performed on seeds harvested in 2 different years (2014 and 2015) resulting in no major difference between the years. Seed storage affected seed viability and dormancy and seedling growth in all 3 grasses. The maximum germination of Festulolium seeds was achieved 6 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The accepted definition of seed vitality is the sum of seed properties that represent seed potential for germination in different conditions (Perry 1980), which determines the complex interaction of genetic and environmental factors (Hodgkin and Hegarty 1978;Finch-Savage and Bassel 2016); cultivation technologies (Bewley et al, 2013); and storage period (Stanisavljević et al, 2020(Stanisavljević et al, , 2019(Stanisavljević et al, , 2016. This also explains the significant influence of the seed lot for seed quality in our tests (Tables 1 to 4).…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accepted definition of seed vitality is the sum of seed properties that represent seed potential for germination in different conditions (Perry 1980), which determines the complex interaction of genetic and environmental factors (Hodgkin and Hegarty 1978;Finch-Savage and Bassel 2016); cultivation technologies (Bewley et al, 2013); and storage period (Stanisavljević et al, 2020(Stanisavljević et al, , 2019(Stanisavljević et al, , 2016. This also explains the significant influence of the seed lot for seed quality in our tests (Tables 1 to 4).…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Festulolium also showed good adaptability to the external environment conditions (Abdelhalim 2016;Humphreys et al, 2013Humphreys et al, , 2014. Studies by Deleuran et al, (2010) gives optimal cultivation technologies for the production of Festulolium seeds, but there is a lack of research and many unknowns about seed storage and aging (Stanisavljević et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All these processes lead to a decrease in the germination rate and an increase in the percentage of dead seeds and abnormal seedlings, which in our study happened with three-year-old seeds. The time after which the seed ageing process begins varies over plant species [19,42].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies, conducted on seeds of marshmallow populations originating from Serbia, indicated that the germination rate of seeds was 29% [10]. Filipović et al [11] stated that the average germination rate of marshmallow seeds amounted to 19.8%, varying from 9.5-26%. On the other hand, Starović et al [12] recorded the average germination rate of marshmallow seeds of 37.7%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the vigor of seeds after storage in these conditions is often low, which inevitably leads to a decrease in GR. An effective way in which to deal with this problem would be increasing the seeding rate with the aim of obtaining a higher GR, although this approach would come at an additional cost (Stanisavljevic et al, 2020). In addition, speci c pretreatment of canola seeds could be an effective method; for example, thermal pretreatment can effectively break seed dormancy and thereby increase the GR and nal yield (Xu et al, 2020).…”
Section: Germination Processmentioning
confidence: 99%